Investigation of Opinions of Nurses Working in Surgical Intensive Care Units about the Participation of Family Members in the Care of Patients during the Dying Process: A Cross-sectional Design - Aynur Koyuncu; Yasemin Eren; Ayla Yava (Galenos Yayinevi, 2024)
Objective: This study was conducted to determine the opinions of nurses working in surgical intensive care units (S-ICU) about the participation of family members (FM) in the care of patients during the dying process. Materials and Methods: Ethical approval was obtained before starting the research. The study was conducted in descriptive type with 81 nurses working in the S-ICU of a training and research hospital between 15 March and 15 April 2022. The data were collected through the descriptive information form and the nurse's opinion determination form created by the researcher. STROBE checklist was used in reporting the research. A p<0.05 value was accepted for statistical significance. Results: The mean age of the nurses participating in the study was 32.39±5.87 years, and the duration of working experience in S-ICUs was 5.69±5.76 years. The rate of nurses wanting the FM of patients in the dying process to participate in the patient care in the intensive care unit is 26%, the rate of not wanting is 57%, and the rate of undecided is 17%. 72.8% of the nurses think that the participation of FM in care is beneficial for the patients, while 27.2% think that it is harmful. It was determined that nurses with working experience had a higher support rate in cases where FMs participated in the care of patients in the dying process (p=0.010) (p<0.05). Conclusion: Although nurses working in S-ICUs think that the participation of FM in the care of patients in the dying process will be beneficial for patients, the rate of support is low.